2000
DOI: 10.1073/pnas.97.10.5328
|View full text |Cite
|
Sign up to set email alerts
|

An ancestral MADS-box gene duplication occurred before the divergence of plants and animals

Abstract: Changes in genes encoding transcriptional regulators can alter development and are important components of the molecular mechanisms of morphological evolution. MADS-box genes encode transcriptional regulators of diverse and important biological functions. In plants, MADS-box genes regulate flower, fruit, leaf, and root development. Recent sequencing efforts in Arabidopsis have allowed a nearly complete sampling of the MADS-box gene family from a single plant, something that was lacking in previous phylogenetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
426
0
9

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 477 publications
(446 citation statements)
references
References 38 publications
11
426
0
9
Order By: Relevance
“…Of the clones from this screen, one started in the MADS box and three began in the I region. SVP was identi®ed as an Arabidopsisexpressed sequence tag with homology to the MADS-box family (Alvarez-Buylla et al, 2000a), and was also cloned by Hartman et al (2000) through transposon tagging. SVP is a repressor of¯owering and is expressed in young leaves and throughout the shoot apical meristem during vegetative development.…”
Section: Proteins That Interact With Calmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the clones from this screen, one started in the MADS box and three began in the I region. SVP was identi®ed as an Arabidopsisexpressed sequence tag with homology to the MADS-box family (Alvarez-Buylla et al, 2000a), and was also cloned by Hartman et al (2000) through transposon tagging. SVP is a repressor of¯owering and is expressed in young leaves and throughout the shoot apical meristem during vegetative development.…”
Section: Proteins That Interact With Calmentioning
confidence: 99%
“…In addition, recent studies have shown that a trio of closely related genes, SEPALLATA1/2/3 (SEP1/ 2/3), are required for petal, stamen and carpel identity, and are thus necessary for the activities of the B-and Cfunction genes (Pelaz et al, 2000). Remarkably, with the exception of the AP2 gene, all the other organ-identity genes belong to the extended family of MADS-box genes, a family that is known to include more than 44 distinct sequences in Arabidopsis (Alvarez- Buylla et al, 2000a;Davies and Schwarz-Sommer, 1994;Purugganan et al, 1995;Rounsley et al, 1995). MADS-domain proteins, well characterized in yeast (MCM1, Ammererer, 1990) and mammals (SRF, Norman et al, 1988), form dimers that bind to DNA and form ternary complexes with many unrelated proteins (Lamb and McKnight, 1991;Shore and Sharrocks, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Floral homeotic class B genes, which comprise AP3/DEF and PI/GLO, are required for petal identity in the second whorl and stamen identity in the third whorl of eudicot flowers (Jack et al 1992(Jack et al , 1994Goto and Meyerowitz 1994;Theissen et al 2000;Alvarez-Buylla et al 2000). AP3/DEF belong to the type II class MADSbox genes, consisting of four distinct regions: a MADS domain (M), an intervening region (I), a keratine-like domain (K), and a C-terminus (C) (Munster et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…MADS genes in Arabidopsis function to regulate diverse developmental events such as flowering time control, meristem identity, floral organ development and fruit development (Alvarez-Buylla et al, 2000b;Initiative, 2000;Riechmann et al, 2000;Theißen et al, 2000). MADS proteins function as dimeric DNA-binding proteins.…”
Section: Introductionmentioning
confidence: 99%